2008
DOI: 10.1016/j.jsbmb.2007.05.034
|View full text |Cite
|
Sign up to set email alerts
|

APRIN is a unique Pds5 paralog with features of a chromatin regulator in hormonal differentiation

Abstract: Activation of steroid receptors results in global changes of gene expression patterns. Recent studies showed that steroid receptors control only a portion of their target genes directly, by promoter binding. The majority of the changes are indirect, through chromatin rearrangements. The mediators that relay the hormonal signals to large-scale chromatin changes are, however, unknown. We report here that APRIN, a novel hormone-induced nuclear phosphoprotein has the characteristics of a chromatin regulator and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…The human Pds5B protein, a paralog of Pds5A, originally isolated as androgene shutoff gene 3 (AS3) from LNCaP prostate cancer cell lines (61) and later designated as APRIN, is a chromatin regulator in hormonal differentiation (62). It shares 73% amino acid identity with Pds5A (Table I) and has been shown to be involved in the regulation of proliferative arrest in cancer cells in response to hormones (61,62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human Pds5B protein, a paralog of Pds5A, originally isolated as androgene shutoff gene 3 (AS3) from LNCaP prostate cancer cell lines (61) and later designated as APRIN, is a chromatin regulator in hormonal differentiation (62). It shares 73% amino acid identity with Pds5A (Table I) and has been shown to be involved in the regulation of proliferative arrest in cancer cells in response to hormones (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…It shares 73% amino acid identity with Pds5A (Table I) and has been shown to be involved in the regulation of proliferative arrest in cancer cells in response to hormones (61,62). It is a putative tumor suppressor (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Cohesin's role in the response to ecdysone involves regulating transcription of the EcR gene (74)(75)(76) and directly regulating ecdysone-responsive gene transcription (76,77). Remarkably, in humans, cohesin also appears to play an important role in the transcriptional response to androgen and estrogen (88,(114)(115)(116).…”
Section: Role Of Cohesin In Hormone-mediated Gene Regulationmentioning
confidence: 99%
“…APRIN evolved by gene duplication from the ancient Pds5 lineage, which shows high conservation from yeast to human (Geck et al, 1999;Maffini et al, 2008). Pds5A, the vertebrate ortholog of this lineage (SCC112 in human) (Kumar et al, 2004;Zheng et al, 2008), is a cohesin-associated protein with long evolution from unicellular eukaryotes (Berney and Pawlowski, 2006).…”
mentioning
confidence: 99%
“…Release 12 of the Pfam-A database (2004) identified that APRIN is a chimeric gene with two successive acquisitions of unique HMG DNA-binding domains (AT-hooks), not present in Pds5A or any of the cohesin factors. Furthermore, APRIN diversified extensively, by 27% from its human Pds5A paralog (Maffini et al, 2008).…”
mentioning
confidence: 99%